(untitled) (Olhar de Professor, 2022)
Teacher training is a space for clashing worldviews. Its importance is revealed both to guarantee the maintenance of the current system, and for the transformation of the reality set. Thus, the question is: what are the main implications of BNC-Training (Resolution n. 02/2019) and BNC-Continuing Training (Resolution n. 01/2020) for the field of teacher training? For this, the objective is to critically analyze the new National Curriculum Guidelines for the initial and continuing training of teachers for basic education and their implications for being and doing a teacher. The method adopted is historical-inductive. The approach is qualitative. The research technique is the bibliographic and documental review. In view of the investigation, it was found that the new guidelines configure a conception of being and doing a teacher centered on pragmatism, immediacy and technicality. On the contrary, we aim at a theoretical-scientific-cultural formation capable of equipping the teacher for an education aimed at the humanization of the students.